Development of Fish-Based Halal Gelatin as an Edible Film Coating Material - Junanda Auditya Onasis; Ela Roswasti Angelia Syeba Ginting (The University of Lampung, 2026)
This study focuses on food products innovation by employing animal-derived material as a basis ingredient for making gelatin. Increasing halal lifestyle provides an opportunity to innovate and answer challenges in meeting consumer needs. The manufacture of animal-based gelatin in the production of edible packaging is a promising solution to reduce plastic waste, but it needs to meet halal requirements. This review analyzes gelatin usage, the application of animal-based food resources, and the potential of edible films as packaging materials in halal product development for Muslim consumers. Edible packaging has great capability to decrease plastic waste and meet the demands of an increasingly conscious market for halal and safety in food products. The results showed that fish gelatin-based edible film is biodegradable, safe for consumption, and able to protect food products from oxidation and microbial contamination because it has a thin layer that can inhibit oxygen. Various studies have also shown that the mechanical and physicochemical characteristics of edible films depend on the fish source and the additives utilized Edible films derived from fish gelatin with halal certification represent a key innovation in supporting halal food industries, minimizing plastic packaging, and improving product preservation time.